Implementasi Pancasila Bagi Pembentuk Karakter Bangsa Sebagai Proses Pembelajaran Terhadap Masyarakat - Azzahra, Kania Syifa; Dewi, Dinie Anggraeni (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
National character is the main capital so that a nation can become a great nation and be able to compete with other nations, however, in reality the Indonesian nation, which is filled with fertile natural gifts, is still unable to get its place as a great nation. The moral development of the nation's young successors, it is increasingly apprehensive, with the development of technology, the teenagers are getting away from manners and norms of decency. Therefore, the values of noble character in Pancasila must be re-implemented in every aspect of the nation's life. This article, which was written using the literature review method, aims to make the Pancasila values which are starting to fade, the values of implementation in society, can grow again and become stronger as the foundation for the nation's development.